Republic of Kazakhstan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This Selected Issues paper analyzes Kazakhstan's recent trends in the fiscal position of general government; the fiscal and oil price vulnerabilities; the fiscal framework; and tax administration. The paper also describes the development of activity in capital markets, the growth of pension funds, and examines the trade movements, exchange rate, and presents an evaluation of external competitiveness of the country. It also provides a statistical appendix report for the Republic of Kazakhstan.